Are the limitations on remedies fair? A comparative study between the US law and Islamic law - Aldossary, Fahad Mubarak (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
This paper addresses similarities and differences between the US law and Islamic law, and considers how each system might benefit from the other. Within the scope of limitations on remedies, the paper explores foreseeability, causation, mitigation, and certainty. How the two systems understand the concepts is described, and the concepts are examined through the lens of fairness. A comparative analysis follows, investigating similarities, divergences, and possible enhancements to the law. The foundation of morality, set in the context of the two systems, establishes grounds for the potential merger of morality and the limitations on remedies. The perspective of justice is a central and crucial point of divergence between the two systems, and the conundrum of flexibility versus faithfulness to the principles of law informs the major findings of the study. Although, there is a noticeable tendency of the two systems to hold a similar legal stance despite their different legal structures.